Skin pathology in kidney transplant recipients. - Correia, C (1992)
Since 1990, 82 unselected renal allograft recipients were evaluated in order to establish the incidence of cutaneous disorders. This pathology was related to the period of immunosuppression according to time of transplantation: 0-3 months; 3-12 months; 12-36 months and beyond 36 months. Most of them were on triple immunosuppression (cyclosporine A, azathioprine and prednisone)--(51); Twenty-two also associated anti-timocyte globulin five days after transplantation; 7 were on Azathioprine and Prednisone and two of them associated Cyclosporine with Prednisone. Iatrogenic manifestations were the most common (80.5%) followed by infections in 63.4% and pre-malignant and malignant cutaneous lesions in 13.4%, other types of manifestations were found in 20.7% of patients. A significant incidence of pre-malignant and malignant lesions confirms other reports, making a dermatological surveillance advisable.